Multi-fuelled Solar Steam Reforming for Pure Hydrogen Production Using Solar Salts as Heat Transfer Fluid. (May 2015) - Giaconia, A.; Monteleone, G.; Morico, B.; Salladini, A.; Shabtai, K.; Sheintuch, M.; Boettge, D.; Adler, J.; Palma, V.; Voutetakis, S.; Lemonidou, A.; Annesini, M.C.; et al.
Abstract: This paper presents a project named CoMETHy (Compact Multifuel-Energy to Hydrogen converter) co-funded by the European Commission under the Fuel Cells and Hydrogen Joint Undertaking (FCH JU). The project is developing an innovative steam reformer for pure hydrogen production to be powered by Concentrating Solar Power (CSP) plants using molten salts as heat transfer fluid. Due to the limitations in the molten salts maximum operating temperature of 550 °C, the reformer should operate at lower temperatures than conventional steam reforming processes. This implies the development of an innovative system, involving different R&D topics presented in this paper.